Comparative Efficacy of Pre-feeding, Post-feeding and Combined Pre- and Post-feeding of Two Microdoses of a Potentized Homeopathic Drug, Mercurius Solubilis, in Ameliorating Genotoxic Effects Produced by Mercuric Chloride in Mice - Datta, Swapna (Oxford University Press, 2004)
Mercury and its derivatives have become an alarming environmental problem, necessitating the search for effective antagonists, including homeopathic drugs, which are generally used in micro doses and are devoid of any palpable side-effects. On the basis of homeopathic similia principle, two potencies of Mercurius solubilis (Merc Sol-30 and Merc Sol-200) were tested by three administrative modes, i.e. pre-feeding, post-feeding and combined pre- and post-feeding, for their possible efficacy in ameliorating mercuric chloride-induced genotoxicity in mice. Healthy mice, Mus musculus, were intraperitoneally injected with 0.06% solution of mercuric chloride at the rate of 1 ml/100 g of body weight, and assessed for genotoxic effects through conventional endpoints. i.e. chromosome aberrations, micronuclei, mitotic index and sperm head abnormality, keeping suitable controls. Mercuric chloride-treated mice were divided into three sub-groups, which were orally administered with the drug prior to, after and both prior to and after injection of mercuric chloride, and their genotoxic effects were analysed at specific intervals of fixation. Mercuric chloride treatment generally produced more chromosome aberations, micronuclei and sperm head anomaly in mice, but the mitotic index appeared to be slightly reduced. While chromosome aberations, micronuclei and sperm head anomaly were generally reduced in the drug-fed series, the mitotic index showed an apparent increase. In most cases, the combined pre- and post-feeding mode appeared to show the maximum amelioration, followed by post-feeding and pre-feeding, in that order. The amelioration by Merc Sol-200 appeared to be slightly more pronounced. We conclude that potentized homeopathic drugs can serve as possible anti-genotoxic agents against specific environmental mutagens, including toxic heavy metals.